Persistent Symptoms in Patients Recovering From COVID-19 in Denmark - Leth, Steffen (Open Forum Infect Dis, 2021)
BACKGROUND: Although persistent symptoms after coronavirus disease 2019 (COVID-19) are emerging as a major complication to the infection, data on the diversity and duration of symptoms are needed. METHODS: Patients aged ≥18 years with a positive polymerase chain reaction (PCR) test for severe acute respiratory syndrome coronavirus 2 who were hospitalized at the Department of Infectious Diseases, Aarhus University Hospital, Denmark, in the period from March 11 to May 15 were offered follow-up after hospitalization. On admission, a comprehensive symptom and medical history was collected, including demographic characteristics, duration of symptoms, comorbidities, and concomitant medications. At discharge, patients were offered follow-up consultations—either by telephone or at an in-person visit—at 6 and 12 weeks at our post-COVID-19 outpatient clinic to assess whether symptoms present at admission had resolved. RESULTS: During the inclusion period, 71 patients were admitted with COVID-19. Of these, 10 patients died, 3 were transferred to another region, 4 declined to participate, and 5 were lost to follow-up before the 12-week evaluation. Thus, 49 patients were included. Overall, 96% reported 1 or more persisting symptoms at 12-week follow-up. The main symptoms were fatigue, dyspnea, cough, chemosensory dysfunction, and headache. CONCLUSIONS: A wide range of persistent symptoms in patients recovering from COVID-19 were present 12 weeks after hospitalization, calling for larger descriptive studies and interdisciplinary research collaborations.